1979
DOI: 10.1177/001440297904500806
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Team Goals: An Essential Step toward Rational Decision Making

Abstract: The assumption that pupil programing team members drawn from the spectrum of the school staffing hierarchy will agree on the goals of the team or will be fully knowledgeable about the team's legally assigned responsibilities is examined. Over 60% of the teams surveyed had less than a three-fourths majority of their members who recognized the team's responsibility to make specific decisions. Furthermore, the MANOVA for role differences was significant for overall recognition of these responsibilities ( p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…The manner in which multidisciplinary teams have operated varies across states, districts, and schools. Historically, the primary goals of these teams were to (a) determine the student's eligibility for special education, (b) determine whether sufficient types of information about the student are available to the placement team before making decisions affecting the student's instructional program, (c) evaluate the educational significance of such data, (d) determine student placement, (e) formulate appropriate year long educational goals and objectives for the student, (f) develop specific short-term instructional objectives for the student, (g) communicate with parents about changes in the student's educational program, ( h ) plan information needed for future review of the student's program and progress, (i) establish the specific date for placement team review, (j) review the continued appropriateness of the student's educational program, and (k) review the student's educational progress (Fenton, Yoshida, Maxwell, & Kaufman, 1979).…”
Section: Multidisciplinary Conferencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The manner in which multidisciplinary teams have operated varies across states, districts, and schools. Historically, the primary goals of these teams were to (a) determine the student's eligibility for special education, (b) determine whether sufficient types of information about the student are available to the placement team before making decisions affecting the student's instructional program, (c) evaluate the educational significance of such data, (d) determine student placement, (e) formulate appropriate year long educational goals and objectives for the student, (f) develop specific short-term instructional objectives for the student, (g) communicate with parents about changes in the student's educational program, ( h ) plan information needed for future review of the student's program and progress, (i) establish the specific date for placement team review, (j) review the continued appropriateness of the student's educational program, and (k) review the student's educational progress (Fenton, Yoshida, Maxwell, & Kaufman, 1979).…”
Section: Multidisciplinary Conferencingmentioning
confidence: 99%
“…Four of these articles were reviews, and 16 were data-based investigations of the functioning of multidisciplinary teams. The majority of the data-based articles were reports of surveys concerning the actual or the perceived practices and attitudes of multidisciplinary team members (Armer & Thomas, 1978;Fenton et al, 1979;Poland, Ysseldyke, Thurlow, & Mirkin, 1979;Smith & Knoff, 1981;Ysseldyke, Algozzine, & Thurlow, 1980;Ysseldyke, Regan, & Schwartz, 1980). Three data-based articles reported direct observational studies of multidisciplinary teams in action (Applied Management Sciences, 1979;Goldstein, Strickland, Tumbull, & Curry, 1980;Ysseldyke, Algozzine, & Thurlow, 1980).…”
Section: An Overview Of Research On Multidisciplinary Teamsmentioning
confidence: 99%
“…Numerous recommendations have been made about ways to improve the team process (Bailey, Helsel-DeWert, Thiele, & Ware, 1983;Fenton, Yoshida, Maxwell, & Kaufman, 1979;Knoff, 1983aKnoff, , 1983bRhode, Leininger, Egan, & Bluhm, 1981;Ysseldyke, Algozzine, & Mitchell, 1982). Yet, it has been suggested that many of the barriers to effective team activities will continue unless a greater commitment to such training is made by teacher trainers (Abelson & Woodman, 1983;Allen-Meares & Pugach, 1982;Garner, 1976;Holland, 1980;Knoff, 1983b;Prasse & Fafard, 1982).…”
Section: Exceptional Childrenmentioning
confidence: 99%
“…not help. (p. 126) Conflict arises when a particular discipline or individual attempts to dominate interdisciplinary staff meetings or fails to recognize the organizational goals of the team (Fenton, Yoshida, Maxwell, & Kaufman, 1979), resulting in behavior from other team members which does not contribute to or facilitate effective decision making (FitzSimons, 1977). Effective group decision making is influenced heavily by the educational background and theoretical foundations each participant receives in training (Garner, 1976), which are undoubtedly heightened by each discipline's lack of knowledge about other participating disciplines.…”
Section: Intermentioning
confidence: 99%